Matopiba em transformação: Ascensão da soja, financeirização da terra e impactos socioeconômicos - Widmarck, Julienne de Jesus Andrade (2023)
This thesis highlights the emergence of the Matopiba region as a vital center for soy production and processing in Brazil. The successful development of soy is emphasized, marked by three fundamental stages: meticulous agricultural research to adapt soy to local conditions, governmental promotion programs to encourage production, and an accelerated expansion of production in the Matopiba region. The complexity of soy development is addressed, focusing on the socio-economic dynamics of the region, including the significant impacts of the financialization of soy, especially on water and marginalized groups. The analysis of financialization and foreignization in post-soy production in the Matopiba region was conducted using the generalized method of moments (GMM), difference-in-differences (DiD), and spatial econometrics. Investment funds, such as the Harvard Management Company (HMC) and TIAA, play a significant role in the financialization and foreignization of land, contributing to the transformation of agricultural land into financial assets and generating potential conflicts. The conclusion reiterates the vital importance of soy in the Brazilian economy and the emergence of Matopiba as a critical area for this production. The thesis represents a significant contribution to economic literature, with a rigorously grounded analysis. However, it also resonates with urgent issues of social justice and sustainability, emphasizing that land, a vital and sacred element, cannot be reduced to a mere commodity. The foreignization and financialization of land, by making land inaccessible to small farmers and local communities, cast a shadow over development. Ultimately, the development of soy in Matopiba, with all its complexities and challenges, is a human story that echoes the fundamental belief that the economy should serve people, not the other way around, and that true and sustainable development can only be achieved when human freedoms are expanded and protected.